Structural Changes of Frozen-Thawed Placenta at Hypothermic Storage - Govorukha, T. P.; Marchenko, L. N.; Repin, N. V. (Problems of Cryobiology and Cryomedicine, 2006)
Structural state of frozen-thawed placenta at its hypothermic storage was studied by the methods of optic and electron microscopies. Hypothermic storage of placenta fragments up to 24 hrs has been shown as not causing a significant effect on terminal villi tissue structure. Prolonged storage up to 48 hrs is accompanied by considerable rearrangements of destructive character.